2019
DOI: 10.4314/ovj.v9i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of enterotoxigenic <i>Escherichia coli</i> isolated from diarrheic calves in Argentina

Abstract: Enterotoxigenic Escherichia coli (ETEC) is the most common and global cause of neonatal calf diarrhea, but there is a little information regarding calf ETEC strains in Argentina. In this study, five ETEC isolates from diarrheic dairy calves (2–10 d old) from Buenos Aires and Cordoba, Argentina were characterized on the basis of virulence gene (VG) pattern, O:H serotyping, hemolytic phenotype, phylogenetic group affiliation, antimicrobial (AM) resistance profile, and presence of integron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…Multidrug resistance (MDR) among E. coli isolates was high, where 61% of E. coli isolates (36/59) showed MDR against two or more antimicrobials, nine isolates (15.3%) exhibit MDR for β-lactam antibiotics, six isolates (10.2%) for non-β-lactam antibiotics, 19 isolates (32.2%) were resistant to both (β-lactams and non-βlactams) and two isolates (3.4%) showed resistance to all antimicrobial used in this study. Our results were compatible with Pasayo et al (2019) who declared that frequent use of antibiotic treatment leading to the production of multiresistant strains that pose a major public health threat. But not aligned with Ahmed et al (2009) who stated that lower multi-antibiotic resistance has been found in E. coli…”
Section: Resultssupporting
confidence: 92%
“…Multidrug resistance (MDR) among E. coli isolates was high, where 61% of E. coli isolates (36/59) showed MDR against two or more antimicrobials, nine isolates (15.3%) exhibit MDR for β-lactam antibiotics, six isolates (10.2%) for non-β-lactam antibiotics, 19 isolates (32.2%) were resistant to both (β-lactams and non-βlactams) and two isolates (3.4%) showed resistance to all antimicrobial used in this study. Our results were compatible with Pasayo et al (2019) who declared that frequent use of antibiotic treatment leading to the production of multiresistant strains that pose a major public health threat. But not aligned with Ahmed et al (2009) who stated that lower multi-antibiotic resistance has been found in E. coli…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, it should be considered that even though the expression of the fimbrial antigen F5 and the production of heat-stable toxin (STa) are highly associated in enterotoxigenic E. coli , some studies have found E. coli F5+ strains without toxigenic potential (i.e., PCR negative for the STa-encoding gene). This could explain why diarrhea was not observed in some of the positive calves [ 77 80 ]. In addition, it is not unexpected to have false negative results using antigen-capture ELISA for F5, as this test has a low sensitivity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of potential virulent F5 fimbria was investigated by subculturing the isolates on pH 7.5 stabile, “minimum of casein” (Minca) agar (Sifin Diagnostics GmbH, Berlin, Germany) as previously published [ 76 ]. Finally, potential hemolytic properties of isolates were interpreted as described with subcultures on Columbia Sheep Blood Agar (Sifin Diagnostics GmbH, Berlin, Germany) [ 77 ]. Growth incubation was carried out for 18 to 24 h at 37 °C at all times.…”
Section: Methodsmentioning
confidence: 99%